Perubahan Faal Paru pada Penderita Efusi Pleura setelah Tindakan Aspirasi Cairan Pleura - Nasution, Morris Shofwan; Widirahardjo, Widirahardjo (Majalah Kedokteran Nusantara The Journal Of Medical School, 2018)
Introduction Pleural effusion is an excessive accumulation of fluid in the pleural space, related to the underlying diseases. Pleural effusion was associated with restrictive ventilatory impairment, and a frequent of symptom with dypsnea. Therapeutic thoracocentesis is aspiration of fluid from the pleural space, the volume removed may be associated with a decrease in the size of thoracic cavity. The aim of this study is to assess the pulmonary function with pleural effusion, performed before and after twenty four hours the therapeutic thoracocintesis Methods This is a propective study with data analysis with paired t-test performed on thirty patients. Subjects were all patients with pleural effusion who were documented clinically and fulfilling inclusion and exclusion criteria between January 2014 and August 2015. Subjects underwent chest x ray to therapeutic thoracocintesis. Spirometry were performed before and after twenty four hours thoracocentesis. Results The study population consisted of thirty patients, 18 male (60%) with a mean age of 49+14.85 years, average weight 52+11.27 kg, average height 159.23+8.52cm, and average of pleural fluid 707+279.25 cc. Pulmonary function before and after twenty four hours thoracocentesis (SVC: 195.31 ml, FVC:165.21 ml, FEV1: 115.40 ml). Statistically significant improvement pulmonary function following after therapeutic thoracocintesis (p<0,05). Conclusion Improvement pulmonary function was observed after therapeutic thoracocintesis in patient with pleural effusion.. Keywords : Pleural effusion, pulmonary function, therapeutic thoracocentesis